New Media dan Penguatan Moderasi Beragama di Indonesia - Hasan Sazali; Ali Mustafa (Jurnal Komunikasi, 2023)
This article aims to analyze the use of YouTube in an effort to strengthen religious moderation in Indonesia on the official YouTube account of the Ministry of Religion of the Republic of Indonesia, "Kemenag RI". The Ministry of Religion was chosen as the subject of the study because it is an institution that is the leading sector in strengthening religious moderation in Indonesia. This study uses a qualitative method. Data were analyzed using qualitative content analysis. This study found several conclusions. First, the use of the YouTube channel in strengthening the issue of religious moderation requires intensification efforts, especially in terms of the variety of themes and the type of content uploaded. Second, the idea of religious moderation that is uploaded revolves around two forms, namely the idea of conception and the idea of action. The notion of conception explains religious moderation as a religious way that is tolerant, spreads compassion, and is non-violent. The idea of action describes a number of programs carried out by the government to strengthen religious moderation in Indonesia. Third, netizens' response to religious moderation content is in two forms of participation, namely affiliation and expression.